The velocity and mixing time scale of the Arctic Ocean Boundary Current estimated with transient tracers - Mauldin, Abigail; Schlosser, P.; Newton, R.; Smethie Jr., W. M.; Bayer, Reinhold; Rhein, M.; Jones, E. Peter (Journal of geophysical research, 2010)
The Arctic Ocean Boundary Current (AOBC) is a persistent, large-scale feature of Arctic circulation that transports water of Atlantic origin around the Eurasian and Canadian Basins. Despite its importance as a link between North Atlantic sea surface temperature and the heat budget of the Arctic Ocean, elements of the pathways of the AOBC are still not well understood. Here we use transient tracer data collected during the 1990s at 22 locations to calculate the velocity and mixing time scale of the AOBC. The apparent spreading velocity derived from correlating 3H-3He ages in the Barents Sea branch water (BSBW) with the distance from its entry point at the Santa Anna Trough is 0.9 cm s−1. To correct this apparent velocity for the effects of mixing along the pathway, the AOBC is modeled as a leaky pipe, and 3H-3He and chlorofluorocarbon data are used to calculate the parameters of its transit time distribution function. The modeled velocity of the AOBC is 2.5 ± 0.5 cm s−1, and the time scale for mixing of waters between the core of the boundary current and the adjacent water masses is 5-10 years. These results imply that the advective time for transport around the perimeter of the Arctic Ocean from the Santa Anna Trough to the southern Canada Basin (approximately 6000 km) is 7.5 years, and the amplitude of a temperature anomaly or salinity anomaly in BSBW should decrease by 50%-75% along this path.